ANALISIS PERSEPSI MAHASISWA TERHADAP MAHASISWI BERCADAR DI UNIVERSITAS RIAU - Nissa Hediyati; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by a phenomenon that occurs in several universities related to the problem of discrimination against veiled female students. Especially the problem at the University of Riau, where there was discrimination against veiled female students during certain courses. The formulation of the problem in this study is how are students' perceptions of veiled students at the University of Riau?. The research objective was to determine student perceptions of veiled students at the University of Riau. This research method is descriptive quantitative, the data collection instrument used in this study is a questionnaire consisting of 6 indicators with 15 questions. The population in this study were all students of the University of Riau. The sample in this study was taken using a proportional sampling technique. Based on the results of the research conducted, it can be concluded that the overall data regarding students' perceptions of veiled female students at the University of Riau are in the